Measuring the "doing-using-interacting mode" of innovation in SMEs - A qualitative approach - Harm Alhusen; Tatjana Bennat; Kilian Bizer; Uwe Cantner; Elaine Horstmann; Martin Kalthaus; Till Proeger; Rolf G. Sternberg; Stefan Töpfer (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2019)
The 'doing-using-interacting mode' of innovation (DUI) is considered an important component of innovative activity. It describes informal innovative activities and thus complements the 'science-technology-innovation mode' (STI) based on research and development. While empirical measurement of the STI mode is well established, proxies for measuring DUI activities are still underdeveloped and no consensus has emerged concerning which intra- and extra-firm processes primarily constitute the DUI mode and how they should be measured. Based upon 81 in-depth interviews with German SMEs and regional innovation consultants, we propose a comprehensive set of 47 indicators comprising both established and new DUI processes for future empirical measurement. We argue that this measurement approach can lead to a more holistic understanding and ultimately quantifiable measurement of DUI innovativeness, which can guide further research and policymaking.
Keywords: O3; O30; O31; R10; 330; DUI; Innovation indicators; learning processes; modes of innovation; STI